PENGARUH SOCIAL MEDIA MARKETING DAN ELECTRONIC WORD OF MOUTH TERHADAP PURCHASE INTENTION MELALUI BRAND IMAGE PADA PENGGUNA TOKOPEDIA, SHOPEE, DAN BUKALAPAK di JAKARTA - Tony Sitinjak; Ericko Pramudita (Jurnal Manajemen, 2021)
Along with techonological development in Industry 4.0, the trading processes have beendeveloped as all trading processes shifted to the electronic concept or integrated with the internet.Also called as e-Commerce. In Indonesia itself, there are 26,2 million units of e-Commerce listedwhich dominated by 3 brands : Tokopedia, Shopee, and Bukalapak. But there are also a lot offactors that effect the consumers’ choices e-Commerce.This study aims to determine the effect of Social Media Marketing and Electronic Word of Mouthon Purchase Intention through Brand Image.The object of the study is the perception of Tokopedia, Shopee, and Bukalapak users on SocialMedia Marketing, Electronic Word of Mouth, Brand Image, and their Purchase Intention. Whilethe subject is Tokopedia, Shopee, and Bukalapak users in Jakarta. This study will be done byusing path analysis by calculating the effect between variables. The result shows that Social Media Marketing, Electronic Word of Mouth and Brand Image arepositively and significantly effect on Purchase Intention. Other than that, Brand Image can be amediating variable between Social Media Marketing and Electronic Word of Mouth on PurchaseIntention.